2018
DOI: 10.1002/cpp.2302
|View full text |Cite
|
Sign up to set email alerts
|

Dispositional self‐compassion and responses to mood challenge in people at risk for depressive relapse/recurrence

Abstract: This paper explores the relationship between dispositional self‐compassion and cognitive emotion regulation capacities in individuals with a history of depression. Study 1 (n = 403) established that self‐compassion was associated with increased use of positive and decreased use of negative strategies, with small to medium sized correlations. Study 2 (n = 68) was an experimental study examining the association between dispositional self‐compassion, use of cognitive emotion regulation strategies, and changes in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 51 publications
2
9
0
1
Order By: Relevance
“…Notably, our LKM-S condition differed from that used in previous research (Arch et al, 2014; Ashar et al, 2016; Fredrickson et al, 2008; Hutcherson et al, 2008; Kok et al, 2013; Weng et al, 2013) by inviting participants to direct compassion to a secure attachment figure/loved one first, and then to direct compassion to the self for several minutes. In support of a possible role of self-compassion for addressing cognitive vulnerability, we have recently shown that individuals with a history of recurrent depression who reported greater self-compassion showed lower self-devaluation and more efficient mood recovery from a sad mood induction (Karl, Williams, Cardy, Kuyken, & Crane, 2018). That the activation of the above physiological pattern partially preceded increased positive and reduced negative self indicates that a state of low physiological arousal (calm and content) in a nonthreatening and nondrive situation may enable openness for altered cognitive appraisals (Fredrickson et al, 2008), but this should be more directly investigated; for example, by using self-referential tasks (Markus, 1977).…”
Section: Discussionmentioning
confidence: 96%
“…Notably, our LKM-S condition differed from that used in previous research (Arch et al, 2014; Ashar et al, 2016; Fredrickson et al, 2008; Hutcherson et al, 2008; Kok et al, 2013; Weng et al, 2013) by inviting participants to direct compassion to a secure attachment figure/loved one first, and then to direct compassion to the self for several minutes. In support of a possible role of self-compassion for addressing cognitive vulnerability, we have recently shown that individuals with a history of recurrent depression who reported greater self-compassion showed lower self-devaluation and more efficient mood recovery from a sad mood induction (Karl, Williams, Cardy, Kuyken, & Crane, 2018). That the activation of the above physiological pattern partially preceded increased positive and reduced negative self indicates that a state of low physiological arousal (calm and content) in a nonthreatening and nondrive situation may enable openness for altered cognitive appraisals (Fredrickson et al, 2008), but this should be more directly investigated; for example, by using self-referential tasks (Markus, 1977).…”
Section: Discussionmentioning
confidence: 96%
“…For example, over a five-month treatment in which self-compassion was present, the participants showed diminished levels of depressive symptoms (Odou and Brinker 2015;Raes 2011). Similarly, Karl et al (2018) suggested that self-compassion is associated with more adaptive responses to mood challenges in individuals with a history of depression. These findings indicated that self-compassion serves as a potentially important protective factor for depression (Wadsworth et al 2018).…”
Section: The Moderating Role Of Self-compassionmentioning
confidence: 99%
“…MBCT-related cultivation of self-compassion also facilitated effective recovery from experimentally induced negative mood in individuals with recurrent depression (Kuyken et al, 2010). Additionally, levels of dispositional self-compassion are associated with more adaptive emotion regulation and more effective repair of negative mood in individuals with current (Diedrich, Grant, Hofmann, Hiller, & Berking, 2014) and remitted depression (Karl, Williams, Cardy, Kuyken, & Crane, 2018). Hence, cultivating self-compassion could be a key mechanism of change via which MBCT is addressing negative self-bias.…”
Section: Introductionmentioning
confidence: 95%